Synthesis Characterization and Antibacterial Activity of 4-Ethynyl Chalcone Derivatives: Life Sciences-Organic Chemistry - Raju, Dachepally; Sreeramulu, J.; Malleswarareddy, P.; Nagaraju, N.; Ramamohan, G. (International Journal of Life Science and Pharma Research, 2022)
Chalcones are polyhydroxylated aryl rings with most of their biological importance. The chemistry of chalcones remained fascinating among researchers due to their simple chemistry, ease of synthesis, large number of replaceable hydrogens and variety of pharmacological activities. In this present investigation our aim is to synthesize a set of 4-ethynylchalcones (3a-j) and to evaluate their Anti-bacterial activity. Synthesis of chalcone derivatives 3a-j was achieved using the classical Claisen- Schmidt reaction. The synthesized chalcone derivatives (3a-j) were tested against Gram negative strains of (i) Escherichia coli (MTCC 443) and (ii) Pseudomonas aeruginosa (MTCC 424) and Gram-positive strains of (iii) Staphylococcus aureus (MTCC 96) and (iv) Streptococcus pyogenes (MTCC 442) using agar well diffusion method. The compounds were dissolved in dimethyl sulphoxide (DMSO) to obtain solutions of concentration 250 μg mL-1. Ciprofloxacin was used as the reference antibacterial drug. Yields of the chalcone derivatives differed from 70 to 85%. The structures of newly synthesized chalcone derivatives 3a-j were established by spectroscopic techniques like 1H NMR, mass and IR spectra of the chalcone derivatives 3a-j are in agreement with the desired structures. Chalcone derivatives (3a-j) characterized by Infrared, ESI-Mass and NMR spectroscopy. Chalcones (3b, 3g, 3h and 3j) with R = 4-OMe, 3-OH, 3-CN and 3,4,5-OMe exhibit good antibacterial activity, the chalcones (3e and 3f) with R = H and 3-NO2 show moderate antibacterial activity and the remaining chalcones in the series such as 3a, 3c, 3d and 3i with R = 4-Br, 3-Br, (3-Br, 4-F) and 4-CH3 display weak antibacterial activity against tested bacterial strains. Now a days health care became a more necessity thing in every one life. So, these chalcone derivatives are may helpful in development of less side effect radical quenching drugs.